ANALISIS PELANGGARAN PRINSIP KESANTUNAN BERBAHASA PADA PERCAKAPAN SISWA KELAS VIII SMP NEGERI 5 ULUNOYO - Silius Hia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This research is motivated by the fact that some students still commit violations of language politeness. The purpose of this study is to describe the principles of language politeness in the conversations of eighth-grade students at SMP Negeri 5 Ulunoyo. This research uses a qualitative approach with descriptive methods. The data source in this study is derived from the transcription of student conversations. The data collection technique used in this research is audio recording. The findings of this study indicate that student conversations contain violations of the principles of language politeness, namely: (1) the maxim of wisdom; (2) the maxim of generosity; (3) the maxim of appreciation; (4) the maxim of appreciation; (5) the maxim of agreement; (6) the maxim of sympathy. It can be concluded that students more frequently violate the maxim of appreciation and are still unable to speak politely. This suggests that politeness in speech determines how one's relationship is in communicating with others as interlocutors or speaking partners. Therefore, it is necessary to apply polite language to maintain harmony in communication. Based on the results of this study, it is recommended that students pay attention to polite language usage, especially in eighth grade at SMP Negeri 5 Ulunoyo. For teachers, it is suggested to apply the principles of language politeness to support successful communication and optimal teaching and learning interactions. For future researchers, more research on language politeness is needed considering its great importance for students' lives.